Transforming Teaching Methods for Business Students: Motivation Focused Approach - Vakhtang Charaia; Tengiz Taktakishvili (European Scientific Journal, ESJ, 2025)
This study examines the factors that influence student motivation in learning, specifically studying the role of feedback and teaching methods. Using regression analysis, we identified two main factors that significantly increase student motivation: constructive feedback and teaching methods that facilitate understanding of study materials. Moreover, relevant literature and contemporary teaching methods were discussed. Results show that students are more motivated when they receive improvement-promoting feedback because it supports their academic growth and engagement. In addition, teaching methods that promote understanding and create an enjoyable learning environment go a long way in promoting sustained motivation. These results highlight the importance of developmental feedback and effective teaching methods in creating a positive and motivating educational experience.